O desejo pela verticalidade - Gonçalves, Joana Carla Soares (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 2000)
Bringing about the preliminary considerations on the issue of verticality, this paper approaches the hypothesis that dictates the inevitability of the tall building, showing its role along the architectural history. The evolving process of the tall building during the 20th century was followed by economic cycles of alternated ascensions and depressions, starting at the american continent during the thirties and reaching Asia at the end of the nineties. For this reason, this critical analysis extrapolates the physical limits of the tower to give a broader give of the implications on the economical aspects related to theme of the verticality. Certainly, the building of towers even before the medieval era, and the accomplishment of the high-rise during the first half of the 20th century, as in the International Style, and finally, the conquest of the super skyscrapers of the nineties, bear a strong will that overcomes the search for profit over the speculative market of buildings